PENGARUH MOTIVASI, IKLIM KERJA DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU - Nasikin, Ali (Students Journal of Economic and Management, 2012)
The aims of this research : (1) to analyze the influence of motivation of teacherâs performance at schools of Institut Indonesia 48 Institution Semarang. (2) to analyze the influence of working atmosphere to teacherâs performance at schools of Institut Indonesia 48 Institution Semarang. (3) to analyze the influence of Principalâs leadership to teacherâs performance at schools of Institut Indonesia 48 Institution Semarang. This is an explanation (qualitative) research. The population is all teachers at schools of Institut Indonesia 48 Institution Semarang., consists of 81 teachers. The sample data is taken using an simple sampling randomly based on slovin technique, where 5% deviation remains 68 teachers in collecting data, the researcher distributes questionnaires using Likert scales which has been tried out. The validity and realibility has been fulfill based on factors analysis, alpha cronbach, and also classical assumption test. The data analysis technique uses double linear analysis model test, R2 test, F-test and t-test hypotesis analysis. The finding research shows : (1) motivation influences the teachers performance positively and significantly at schools of Institut Indonesia Institution 48 Semarang. (2) Working atmosphere influences the working atmosphere of teachers positively and significantly at schools of Institut Indonesia Institution 48 Semarang. (3) The principel leadership influences the teachers working atmosphere positively and significantly at schools of Institut Indonesia Institution 48 Semarang. Key Words : motivation, working atmosphere, Principalâs leadership and teacherâs performance